MANAGERIAL PERFORMANCE: THE MEDIATING ROLE OF STRATEGY MANAGEMENT ACCOUNTING TECHNIQUES ON COMPETITIVE ADVANTAGE AND ORGANIZATION PERFORMANCE - Listya Sugiyarti; Nur Asmilia (EAJ (Economic and Accounting Journal), 2020)
This study aims to examine Managerial Performance as Strategic Management Accounting Technique for Competitive Advantage and Organization Performance in banking companies in the Tangerang region, Indonesia. In this study utilizing primary data in the form of questionnaires distributed to managers in banking companies in Tangerang region, Indonesia. This study applied Structure Equation Modeling analysis techniques with Amos software program tools, while a number of respondents are 73 managers. From the results of the tests which have been obtained that Managerial Performance as Strategic Management Accounting Techniques had a positive and significant effect on Competitive Advantage. There was not significant effect of Competitive Advantage on Organization Performance, and Managerial Performance as Strategic Management Accounting Techniques did not have a positive and significant effect on Organization Performance in banking companies in Tangerang Region